The Kaleidoscope of Microglial Phenotypes - Dubbelaar, Marissa L.; Kracht, Laura; Eggen, Bart J. L.; Boddeke, Erik W. G. M. (Frontiers in Immunology, 2018)
Abstract Gene expression analysis of microglia, the tissue-resident macrophages of the central nervous system, has led to the identification of homeostatic as well as neurodegenerative disease-specific core gene signatures of microglia phenotypes, driven by epigenetic mechanisms. Upon alterations in the neural microenvironment, for instance during disease, microglia can switch phenotypes- generally referred to as “microglia activation. Phenotypical switches of microglia due to environmental changes can be imagined as the different colorful crystal formations (microglia phenotypes) that change upon rotation (environmental changes) of a kaleidoscope. In this review, we will discuss microglia phenotypes in relation to neurodevelopment, homeostasis and neurodegenerative diseases, based on transcriptome studies as well as the complexity of a microglial core gene signature associated with multiple diseases.